2009
DOI: 10.1128/cvi.00327-08
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Immunity to Clade 2 Strains of Influenza Virus A Subtype H5N1 Induced in Adults and Elderly Patients by Fluval, a Prototype Pandemic Influenza Virus Vaccine Derived by Reverse Genetics, Formulated with a Phosphate Adjuvant, and Directed to Clade 1 Strains

Abstract: High fatality rates and multiple cases of transmission of avian H5N1 influenza viruses to humans illustrate the urgent need for an efficacious, cross-protective vaccine against H5N1 strains. Extensive genetic characterization of H5N1 strains has elucidated the natural evolutionary relationship of these strains, linking groups known as clades to a common ancestor. Although the clades and subclades probably differ sufficiently in their antigenic structure to warrant the preparation of different vaccines, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…We are now extending these studies to children, as a trial with a 6-g dose of the present vaccine in pediatric subjects was recently completed (26). Also, studies of cross-reactive immunity in a subset of the present study population were recently published (9).…”
Section: Discussionmentioning
confidence: 96%
“…We are now extending these studies to children, as a trial with a 6-g dose of the present vaccine in pediatric subjects was recently completed (26). Also, studies of cross-reactive immunity in a subset of the present study population were recently published (9).…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported the results of several clinical trials showing convincing immunogenicity and even crossreactive immunity in adult and elderly patients after one injection of a 6-g dose of a licensed monovalent prepandemic influenza A virus H5N1 vaccine (Fluval H5N1; Omninvest, Hungary) or a licensed monovalent pandemic H1N1 vaccine (Fluval P; Omninvest, Hungary) produced by essentially the same methods as reported for this trial (8,(14)(15)(16)(17)(18). Thus, the findings of this trial accord with our previous work with whole-virion, inactivated, adjuvanted prototype prepandemic and pandemic influenza vaccines (8,(14)(15)(16)(17)(18). We now extend the findings of strong immunogenicity with only 6 g of hemagglutinin to trivalent seasonal vaccines as well, as we found that the administration of the reduced-dose seasonal trivalent influenza vaccine containing 6 g of hemagglutinin/strain was safe in adult and elderly patients and met international criteria for licensing (5).…”
Section: Discussionmentioning
confidence: 97%
“…The reduced-dose vaccine (Fluval K, an inactivated, wholevirion, trivalent vaccine with 6 g of HA/strain/0.5 ml content and aluminum phosphate gel adjuvant; lot no. FL-K-004) was produced by Omninvest Ltd. (Budapest, Hungary) as described previously (8,(14)(15)(16)(17)(18)(19). With the exception of the antigen amount, the vaccine was prepared by the same method as for the licensed seasonal influenza vaccine Fluval AB (19) and the licensed prepandemic vaccine Fluval H5N1 and the licensed pandemic H1N1 vaccine Fluval P (8,(14)(15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These variants have been classified into genetically distinct clades to facilitate comparison of H5N1 isolates. 61 An important component of clinical trials 45,46,[62][63][64][65] and animals model studies 54,58,66,67 has therefore been determination of the breadth of the vaccineinduced antibody response against these different clades. In all of these studies, cross-reactive antibody could be demonstrated against H5N1 viruses representing several clades and subclades and the addition of an adjuvant appeared to be instrumental in achieving this ( Table 3).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%